RELEVANCE OF RISK AND CRIMINOGENIC NEEDS ASSESSMENT IN REHABILITATION PROGRAMS AT PENITENTIARIES - Andriyan, Ferry; Rahayu, Mulyani (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The increasing crime rate has led to overcrowding in correctional facilities. This condition poses a barrier to the implementation of rehabilitation programs, which are the rights of every inmate during their incarceration. Given the diversity of inmates' backgrounds, in-depth identification is needed to assess each individual's criminogenic needs. Risk and needs assessment instruments are used to evaluate the risk of recidivism among inmates and to identify criminogenic factors. The results of these assessments should serve as a reference in the formulation of rehabilitation programs. However, in practice, the assessment results are often not used as the primary basis for providing rehabilitation programs. This study aims to determine the relevance of risk and criminogenic needs assessments in the implementation of inmate rehabilitation. The research employs a qualitative method with data collection techniques including literature review, interviews, and documentation. The results indicate that risk and needs assessments remain relevant to the condition of the correctional system in Indonesia, particularly in supporting the adopted philosophy of social reintegration. However, there are several challenges in implementation, such as the unavailability of assessors in correctional facilities, leading assessments to be conducted by social workers and correctional staff. Additionally, the available rehabilitation programs are still limited, resulting in not all recommendations from the assessments being accommodated through existing rehabilitation programs. In conclusion, assessments are highly relevant to rehabilitation programs for inmates, and future developments in assessment and the digitalization of assessments are needed. Keywords: Assessment; Rehabilitation; Inmates